Reduction degree and property study of graphene nanosheets prepared with different reducing agents and their applicability as a carrier of the Ru(phen)3Cl2 luminescent sensor for DNA detection1. Issue 34 (15th April 2015) - Li, Hongjuan; Wen, Jia; Yu, Ruijin; Bai, Caihui; Xu, Yongqian; Liu, Zong-Huai; Sun, Shiguo
<x xml:space="preserve">Abstract</x> Recently, graphene nanosheets (GNS) have been widely investigated and used in capacitors, catalysts, biological/chemical sensors, etc.